Multimedia courseware for rapid prototyping - Ke, Brendan Deng Yao. (2010)
RP technology also known as Additive Manufacturing (AM) is becoming increasingly important and complex today. Therefore, it is essential that this knowledge can be taught and learnt by interested parties with ease. Multimedia teaching tools have been heavily employed in recent years as they are advantageous in many aspects.